PERAN ALUMNI DALAM RANGKA PENINGKATAN MUTU PENDIDIKAN DAN KUALITAS ALMAMATER - Agustinus Supriyadi (Lembaga Penelitian STKIP Widya Yuwana, 2019)
Education is the primary means for the successful of national development. This is because education is expected to form the quality of human resources neededfor development itself. Human resource is a prerequisite for the existence of the quality of an educational institution. However, the quality of an educational institution is influenced by many factors, among others are means of infrastructure, systems and dynamics of educational activities, mentality and quality of educators, and the role of alumni who have lived and involved throughout various fields work. Therefore, the development of educational institution is not only focused on providing educational inputs but also has to pay more attention to the education process itself. Alumni have a special relationship and bond to the educational institution which formed and educated them before. Therefore, Alumni are expected to be more participating in improving the quality of educational institution where they were educated before. In other side, Almamater is also expected to continously giving a warm greeting to those alumni since they are individuals who are expected to devote more and more their knowledge, experiences dan times for the development of Almamater. The atmosphere can be well established if both Almamater and Alumni is expected to be more open and please to one another.